EVALUASI KINERJA GEDUNG A UNIVERSITAS PEMBANGUNAN JAYA DENGAN PUSHOVER ANALYSIS BERDASARKAN FEMA 356 - Muhammad Irfan.; Agustinus Agus Setiawan (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2023)
Indonesia is a country with a high potential for earthquake risk, therefore every building must be designed in such a way, so the impact of damage caused by an earthquake can be minimized. Each Existing building structure also needs to be analyzed for its performance against earthquake loads. The main rule in designing an earthquake-resistant building is that structural elements may be damaged but must not fail or collapse during a strong earthquake. This study aims to analyze the performance of building structures based on FEMA 356 standards, by taking a case study of the structure of Tower A of Pembangunan Jaya University. The method used is the pushover analysis method using the Etabs V.16 application. The results of the nonlinear static analysis produce an output value which is then calculated using the FEMA 356 standard. The results of the analysis show that Tower A of Pembangunan Jaya University, which is an open frame structure made of reinforced concrete, has an Immediate Occupancy performance level, which means that if the structure is hitting by an earthquake with return period of 50 years, the building has no significant damage to the structural components. The stiffness and strength of the building is almost the same as before the structure was hit by the earthquake. Meanwhile, the building has a displacement value of 0.383 meters, this value is still smaller than the displacement value based on FEMA 356 calculations which is quite large, namely 0.618 meters in the x direction and 0.542 meters in the y direction.